467 Organisational approach to occupational health and wellbeing in a national rehabilitation hospital. (24th April 2018) - Curtis, R; More O'Ferrall, J
Abstract : Introduction: Working in a rehabilitation facility is a demanding job, physically, psychologically and emotionally. The leadership of the National Rehabilitation Hospital (NRH) has taken an exemplary role in addressing these risks by creating a positive working environment group to support an organisational approach to occupational health and wellbeing under the domains of, physical, psychological, environmental and social wellbeing. Methods: Several initiatives have been offered to staff under various domains. Physical Wellbeing- health screening programmes, vaccination programmes, healthy eating and weight loss programmes, physical activity programmes, smoking cessation programmes, absence management programmes. Psychological wellbeing offers staff occupational health advice and support, employee assistance programme, annual staff surveys and focus groups, staff coaching, annual staff recognition day, flexible working patterns, multiple leave options, financial advice and in house saving options. Social wellbeing encourages social gatherings and supports staff to deal with interpersonal difficulties through, dignity at work training and conflict coaching. Intellectual wellbeing in NRH facilitates on going education through in-house training such as mandatory and organisational trainings, grand rounds and peer reviews, full or part funding is made available to staff for further studies and conference attendance and staff recognition days. Environmental wellbeing is co-ordinated by the quality, safety and risk department and managed through an extensive organisation wide risk register supported by the quality, safety and risk committee, hygiene and infection prevention and control committee and radiation safety committee. Result: Since the formation of the Positive Working Environment Group, staff engagement in staff survey has increased from 41% in 2012 to 63% in 2016. Staff absence has decreased and staff report feeling more supported by management and peers. Discussion: By creating a co-ordinated organisation wide approach to health and wellbeing NRH has improved the working environment for staff and clients.